Determinants of Taste Preference and Acceptability: Quality versus Hedonics - Loney, Gregory C. (Society for Neuroscience, 2012)
Several methods exist for reliably determining the motivational valence of a taste stimulus in animals, but few to determine its perceptual quality independent of its apparent affective properties. Individual differences in taste preference and acceptability could result from variance in the perceptual qualities of the stimulus leading to different hedonic evaluations. Alternatively, taste perception might be identical across subjects, but the processing of the sensory signals in reward circuits could differ. Using an operant-based taste cue discrimination/generalization task involving a gustometer, we trained male Long–Evans rats to report the degree to which a test stimulus resembled the taste quality of either sucrose or quinine regardless of its intensity. The rats, grouped by a characteristic bimodal phenotypic difference in their preference for sucralose, treated this artificial sweetener as qualitatively different—compared to sucralose-avoiding rats, the sucralose-preferring rats found the stimulus much more perceptually similar to sucrose. Although the possibility that stimulus palatability may have served as a discriminative cue cannot entirely be ruled out, the profile of results suggests otherwise. Subsequent brief-access licking tests revealed that affective licking responses of the same sucralose-avoiding and -preferring rats differed across concentration in a manner approximately similar to that found in the stimulus generalization task. Thus, the perceived taste quality of sucralose alone may be sufficient to drive the observed behavioral avoidance of the compound. By virtue of its potential ability to dissociate the sensory and motivational consequences of a given experimental manipulation on taste-related behavior, this approach could be interpretively valuable.